Use of “Tanya Saja” Application as An Andriod-Based Counseling Medium: Penggunaan Aplikasi Tanya Saja Sebagai Media Konseling Berbasis Andriod - Yanti, Irma; Suhartini, Leni; Suryani, Lilis; Hannie (Universitas Muhammadiyah Sidoarjo, 2022)
Background: During the Covid-19 pandemic, promotive and preventive efforts online with reliable sources are the best choice for the public. Tanya Saja application was formed as an android-based midwifery counseling media that can meet information about the health of mothers and children. This research aims to find out the characteristics, interests, information, perceptions and knowledge before the use of the Tanya Saja application. Method: This study uses the cross-sectional method, data collection was carried out in July - December 2021, at posyandu Kemuning VII Karawang Kulon Village Tanjungpura Karawang Health Center Working Area involving 57 participants, where the participants of the activity were village midwives, kader and posyandu participants including pregnant women, mothers who have babies, toddlers and children, women of childbearing age. Analyze the data using chi square with a signification rate of 5%. Results: the average ask application user who is 33 years old, has a high school education background of 50.9%, works as a housewife 89.5% has knowledge of good midwifery teleconsultation as much as 82.5%, has a good perception of the application tanya saja as much as 38.6%, exposed to information The health of mothers and children from the tanya saja application as much as 91.2%, have an interest in using the tanya saja application as much as 81.1%. The variables related to the use of the tanya saja application are the age of the respondent (p 0.015), information (p 0.000), and interest (p 0.000). As for the education and perception variables have no relationship with the use of the application. Conclusion: Tanya Saja application can be used as a medium for midwifery counseling during the Covid-19 pandemic.